2002
DOI: 10.1177/095632020201300602
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the IMPDH Enzyme as Potential Anti-Bovine Viral Diarrhoea Virus Agents

Abstract: Ribavirin and mycophenolic acid (MPA) are known inhibitors of the IMPDH enzyme (E.C. 1.1.1.205). This enzyme catalyzes the conversion of inosine monophosphate to xanthine monophosphate, leading eventually to a decrease in the intracellular level of GTP and dGTP. The antiviral effect against bovine viral diarrhoea virus (BVDV) of 15 analogues related to MPA was determined. MDBK cells were infected with the cytopathic strain of BVDV in presence or absence of test compounds. Viral RNA was extracted from the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…It has also been shown that FdC could be phosphorylated by the HSV-1 viral thymidine kinase (19). However, when FdC was tested against the cytopathogenic BVDV strain NADL in MDBK cells (14), the compound was unable to inhibit the production of viral RNA in the culture supernatant (EC 90 , Ͼ100 M; data not shown) and was not cytotoxic (CC 50 , Ͼ100 M). The inactivity of FdC in the MDBK-cpBVDV model may have resulted from (i) poor initial activation to FdC-monophosphate by the bovine deoxycytidine kinase, (ii) rapid deamination by the bovine cytidine deaminase or deoxycytidine deaminase to the inactive 2Ј-deoxy-2Ј-fluorouridine (FdU), or (iii) an inability of BVDV polymerase to recognize FdCTP as a substrate.…”
mentioning
confidence: 96%
“…It has also been shown that FdC could be phosphorylated by the HSV-1 viral thymidine kinase (19). However, when FdC was tested against the cytopathogenic BVDV strain NADL in MDBK cells (14), the compound was unable to inhibit the production of viral RNA in the culture supernatant (EC 90 , Ͼ100 M; data not shown) and was not cytotoxic (CC 50 , Ͼ100 M). The inactivity of FdC in the MDBK-cpBVDV model may have resulted from (i) poor initial activation to FdC-monophosphate by the bovine deoxycytidine kinase, (ii) rapid deamination by the bovine cytidine deaminase or deoxycytidine deaminase to the inactive 2Ј-deoxy-2Ј-fluorouridine (FdU), or (iii) an inability of BVDV polymerase to recognize FdCTP as a substrate.…”
mentioning
confidence: 96%
“…One of the most important questions in testing antimetabolites for antireplicon (or antiviral) activity is whether induction of the cytostatic and/or cytotoxic condition can be separated from specific antiviral activity, since "dead cells don't make virus." There are many reports in which specific antiviral activity has been ascribed to antimetabolites (1,11,22,23,28), but to date, no systematic study has been conducted to determine their effects on HCV subgenomic replicon. In addition, the antiviral action of antimetabolites such as ribavirin remains controversial (17,18,29).…”
mentioning
confidence: 99%
“…Only few examples are reported for the treatment of BVDV such as acridones [21] ribavirin and mycophenolic acid (MPA) [22], and iminosugars [23]. In connection with our strategy in synthesis of new amino acid derivatives [24,25], we report here the synthesis of new peptides bearing naphthalene residue as potential antiviral and antitumor candidates.…”
Section: Introductionmentioning
confidence: 98%